Plant Life : a brief history. - Essig, Frederick B. (Oxford University Press, 2015)
Charles Darwin, the father of the theory of evolution, described the evolutionary origin of flowering plants as an ""abominable mystery."" Flowering plants - which appeared abruptly during the late Cretaceous Period - the origins of photosynthesis, and the early evolution of land plants are some of earth's most mysterious breakthroughs. The first seed plants appear in the fossil record about 350 million years ago, and flowering plants first appear approximately 120 million years ago, but the transitions between these major forms of plant life remain obscure. Prior to each breakthrough was a lo.